Soil Fungal Community Characteristics and Mycelial Production Across a Disturbance Gradient in Lowland Dipterocarp Rainforest in Borneo - Robinson, Samuel J. B.; Elias, Dafydd; Johnson, David; Both, Sabine; Riutta, Terhi; Goodall, Tim; Majalap, Noreen; McNamara, Niall P.; Griffiths, Robert; Ostle, Nick (Frontiers in Forests and Global Change, 2020)
The rainforests of SE Asia are a global hotspot of biodiversity and forest degradation. Selective logging and forest conversion to oil palm plantation has major implications for biogeochemical cycling and carbon storage that are underpinned by plant-soil interactions. Soil fungi are key regulators of carbon and mineral nutrient flows between above- and below-ground organisms, yet understanding of fungal community-productivity relationships in hyper-diverse tropical forests is lacking. Recent studies suggest sensitivity of soil fungal communities to land-use change, although impacts on fungal productivity remain largely unresolved. To address this gap, we installed hyphal in-growth bags for six months in old-growth (OG), selectively-logged (SL) forest and oil palm plantation (OP) in Bornean lowland rainforest. Mycelial (actively foraging) fungal communities were characterised by ITS amplicon sequencing, and mycelial production estimated by measurement of fungal hyphae. Mycelial fungal community compositions were similar in OG and SL forest, whereas OP had significantly different communities of saprotrophic, mycorrhizal, and pathogenic fungi. In particular, mycorrhizal relative abundance and diversity and mycelial production was reduced. However, due to restricted sampling replication in OP, effects associated with site could not be excluded. In forest plots (OG & SL), we further explored the broader drivers of mycelial fungal communities using tree community, structure and productivity data, and soil and environmental properties. Forest mycelial community dissimilarities were related to soil and vegetation characteristics. Mycelial production was independent of fungal community or vegetation attributes but positively related to soil inorganic P concentrations. Changes in relative abundances of mycorrhizal types were also found with selective logging, which may have implications for carbon storage capacity in these forests, while an apparent retention of mycorrhizal mycelium in SL forest may act as a reservoir of inoculum that could aid forest restoration. Our results show that conversion of rainforest to oil palm plantation has significant consequences for fungal diversity-productivity relationships with implications for nutrient and carbon dynamics and restoration over large spatial scales.